A pre-clinical validation plan to evaluate analytical sensitivities of molecular diagnostics such as BD MAX MDR-TB, Xpert MTB/Rif Ultra and FluoroType MTB. - Markus Beutler; Sara Plesnik; Marina Mihalic; Laura Olbrich; Norbert Heinrich; Samuel Schumacher; Michael Lindner; Ina Koch; Wolfgang Grasse; Christoph Metzger-Boddien; Sabine Hofmann-Thiel; Harald Hoffmann (PLoS ONE)
Rapid diagnosis of tuberculosis (TB) and antibiotic resistances are imperative to initiate effective treatment and to stop transmission of the disease. A new generation of more sensitive, automated molecular TB diagnostic tests has been recently launched giving microbiologists more choice between several assays with the potential to detect resistance markers for rifampicin and isoniazid. In this study, we determined analytical sensitivities as 95% limits of detection (LoD95) for Xpert MTB/Rif Ultra (XP-Ultra) and BD-MAX MDR-TB (BD-MAX) as two representatives of the new test generation, in comparison to the conventional FluoroType MTB (FT-MTB). Test matrices used were physiological saline solution, human and a mucin-based artificial sputum (MUCAS) each spiked with Mycobacterium tuberculosis in declining culture- and qPCR-controlled concentrations. With BD-MAX, XP-Ultra, and FT-MTB, we measured LoD95TB values of 2.1 cfu/ml (CI95%: 0.9-23.3), 3.1 cfu/ml (CI95%: 1.2-88.9), and 52.1 cfu/ml (CI95%: 16.7-664.4) in human sputum; of 6.3 cfu/ml (CI95%: 2.9-31.8), 1.5 cfu/ml (CI95%: 0.7-5.0), and 30.4 cfu/ml (CI95%: 17.4-60.7) in MUCAS; and of 2.3 cfu/ml (CI95%: 1.1-12.0), 11.5 cfu/ml (CI95%: 5.6-47.3), and 129.1 cfu/ml (CI95%: 82.8-273.8) in saline solution, respectively. LoD95 of resistance markers were 9 to 48 times higher compared to LoD95TB. BD-MAX and XP-Ultra have an equal and significantly increased analytical sensitivity compared to conventional tests. MUCAS resembled human sputum, while both yielded significantly different results than normal saline. MUCAS proved to be suitable for quality control of PCR assays for TB diagnostics.